KORUPSI DALAM TINJAUAN HUKUM ISLAM - M.A, Amelia (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2010)
Trusted (amanah) and honest are among the principles of the values of Islamic teaching. Consequently, corruption is a clear form of violation toward the principles of amanah and is regard as the violent stealth of others’ property. This is definitely unaccepted, illegal, and sinful behavior. As a result, the corruptor will be punished both in the world and the day after.